Renewable energy curtailment: A case study on today's and tomorrow's congestion management. (January 2018) - Schermeyer, Hans; Vergara, Claudio; Fichtner, Wolf
Abstract: This work aims at contributing to the development of congestion management in power systems facing a strong expansion of renewable electricity generation. We address a comparatively new but increasingly important challenge to electricity markets with a uniform price zone: Renewable curtailment due to grid constraints. Our goal is to provide a model framework suitable to investigate the impact of expanding the grid operator's flexibility under varying congestion management regimes. We aim to expose the limitations of the current regime and to present a favorable alternative. For our analysis, we develop an optimal power flow program to replicate the current congestion management regime for distribution grids with high penetration of distributed generation in Germany. Furthermore, we introduce district heating as additional flexibility option and investigate the impact under different approaches to congestion management. Our results suggest that introducing additional flexibility, while keeping the current congestion management regime, bears significant risk to increase the cost of congestion management. Adjusting the regime to take into account economic criteria, as outlined in this work, eliminates this risk and grants direct control on the trade-off between curtailment and cost. Highlights: Renewable energy curtailment in Germany has increased sharply over the last years. Distribution grid constraints are more relevant than reflected by current discussion. Additional flexibility options for congestion management may strongly increase cost. Presented congestion management approach enables to trade-off cost and curtailment.